“Estudio socio-económico del cultivo de cacao (Theobroma cacao L.) En la parroquia Febres Cordero, cantón Babahoyo” - Carbo Avellán, Suany Carolina (2018)
SUMMARY “Socioeconomic study of cocoa cultivation (Theobroma cacao L) in the parish Febres Lamb canton Babahoyo” AUTHOR: Suanny Carolina Carbo Avellán TUTOR: Ing. Agr. Ricardo Chávez Betancourt, MsC. The work was carried out in the Febres Cordero parish of the Babahoyo canton of the Province of Los Ríos, with the objective of diagnosing the socioeconomic status of cocoa producers in the sector. Within the project is verified the variety of cocoa that cocoa crops have in which, 92% use CCN-51 and their destination of sale is locally. Another point that could be analyzed is the profitability of the production according to the investment, which was found to be very profitable for a percentage estimated at 95% of the cocoa farmers in the sector. Keywords: Socioeconomic, crops, CCN-51.